Popular Attitudes toward Markets and Democracy: Russia and United States Compared 25 Years Later - Boycko, Maxim; Shiller, Robert J. (American Economic Review, 2016)
We repeat a survey we did in the waning days of the Soviet Union (Shiller, Boycko and Korobov, AER 1991) comparing attitudes towards free markets between Moscow and New York. Additional survey questions, from Gibson Duch and Tedin (J. Politics 1992) are added to compare attitudes towards democracy. Two comparisons are made: between countries, and through time, to explore the existence of international differences in allegiance to democratic free-market institutions, and the stability of these differences.